Seriality, influence and adaptation in Ahmet Mithat's novels Hasan Mellâh and Zeyl-i Hasan Mellâh - Topçuoğlu, Arif Can. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
The first examples of the novel in Turkish literature were given in the middle of the nineteenth century, in the form of serial. During this period, Ottoman intellectuals introduced this genre to the readers via translations from especially French literature, and then, wrote the first examples in various creative ways. The relationship that early novelists established with Western literature has been one of the most cited issues in the history of Turkish literature. The dominant discourse claims that the first novelists were apprentices who tried to copy the Western novels into Turkish which makes the first novels become cheap imitations of the Western ones. Besides, the fact that first novels are actually serial novels was ignored in these research studies. Thus, the narrative techniques of serial novels were examined with the perception of contemporary novels hence, these novels considered as flawed. From this point forth, the first target of this thesis is to consider the influence matter from a different angle and also, bring forward the seriality issue which is ignored by literary historians. To do so, this study will focus on Ahmet Mithat’s first novel Hasan Mellâh Yahut Sır İçinde Esrar (1874) and its sequel Zeyl-i Hasan Mellâh Yahut Sır İçinde Esrar (1875) in terms of seriality, influence, and adaptation. The main aim in the thesis is to show source texts that Ahmet Mithat was influenced during the adaptation process, how and why he preferred to change these texts and what role seriality played in this process.